Compromising KCC2 transporter activity enhances the development of continuous seizure activity. (September 2016) - Kelley, Matthew R.; Deeb, Tarek Z.; Brandon, Nicholas J.; Dunlop, John; Davies, Paul A.; Moss, Stephen J.
Abstract: Impaired neuronal inhibition has long been associated with the increased probability of seizure occurrence and heightened seizure severity. Fast synaptic inhibition in the brain is primarily mediated by the type A γ-aminobutyric acid receptors (GABAA Rs), ligand-gated ion channels that can mediate Cl − influx resulting in membrane hyperpolarization and the restriction of neuronal firing. In most adult brain neurons, the K + /Cl − co-transporter-2 (KCC2) establishes hyperpolarizing GABAergic inhibition by maintaining low [Cl − ]i . In this study, we sought to understand how decreased KCC2 transport function affects seizure event severity. We impaired KCC2 transport in the 0-Mg 2+ ACSF and 4-aminopyridine in vitro models of epileptiform activity in acute mouse brain slices. Experiments with the selective KCC2 inhibitor VU0463271 demonstrated that reduced KCC2 transport increased the duration of SLEs, resulting in non-terminating discharges of clonic-like activity. We also investigated slices obtained from the KCC2-Ser940Ala (S940A) point-mutant mouse, which has a mutation at a known functional phosphorylation site causing behavioral and cellular deficits under hyperexcitable conditions. We recorded from the entorhinal cortex of S940A mouse brain slices in both 0-Mg 2+ ACSF and 4-aminopyridine, and demonstrated that loss of the S940 residue increased the susceptibility of continuous clonic-like discharges, an in vitro form of status epilepticus. Our experiments revealed KCC2 transport activity is a critical factor in seizure event duration and mechanisms of termination. Our results highlight the need for therapeutic strategies that potentiate KCC2 transport function in order to decrease seizure event severity and prevent the development of status epilepticus. Highlights: KCC2 transport plays a role in determining seizure event duration. Reducing KCC2 transport activity prevents seizure event termination. KCC2-S940 phosphorylation limits the onset of continuous seizure activity.